A Modified Electrostatic Adsorption Apparatus for Latent Fingerprint Development on Unfired Cartridge Cases2. Issue 3 (13th December 2016) - Xu, Jingyang; Zhang, Ziyuan; Zheng, Xiaochun; Bond, John W.
Abstract: Visualization of latent fingerprints on metallic surfaces by the method of applying electrostatic charging and adsorption is considered as a promising chemical‐free method, which has the merit of nondestruction, and is considered to be effective for some difficult situations such as aged fingerprint deposits or those exposed to environmental extremes. In fact, a portable electrostatic generator can be easily accessible in a local forensic technology laboratory, which is already widely used in the visualization of footwear impressions. In this study, a modified version of this electrostatic apparatus is proposed for latent fingerprint development and has shown great potential in visualizing fingerprints on metallic surfaces such as cartridge cases. Results indicate that this experimental arrangement can successfully develop aged latent fingerprints on metal surfaces, and we demonstrate its effectiveness compared with existing conventional fingerprint recovery methods.